Sequencing Analysis and Phylogenetic Tree of HPV Isolated from Breast Cancer Patients at Thi-Qar Province/Iraq - Bushra Jabbar Hamad; Manal Badi Saleh (University of Thi-Qar Journal of Science, 2020)
Genetic variety examination has demonstrated fundamental to the understanding of the epidemiological and developmental history of Papillomavirus (HPV), for the development of accurate diagnostic tests and for efficient vaccine design. The HPV nucleotide diversity has been investigated widely among high-risk HPV types. To make the nucleotide sequence of HPV and do the virus database in Thi-Qar province, and compare sequences of our isolates with previously described isolates from around the world and then draw its phylogenetic tree, this study done. A total of 6 breast formalin-fixed paraffin-embedded (FFPE) of the female patients were included in the study, divided as 4 FFPE malignant tumor and 2 FFPE of benign tumor. The PCR technique was implemented to detect the presence of HPV in breast tissue, and the real-time PCR used to determinant HPV genotypes, then determined a complete nucleotide sequence of HPV of L1 capsid gene, and draw its phylogenetic tree. The nucleotide sequencing finding detects a number of substitution mutation (SNPs) in (L1) gene, which have not been designated before, were identified once in this study population, and revealed that the HPV16 strains have the evolutionary relationship with the South African race, while, the HPV33 and HPV6 showing the evolutionary association with the North American and East Asian race, respectively.